INTERNAL QUALITY ASSURANCE (IQA) SYSTEM AT MYKOLAIV V. O. SUKHOMLYNSKYI NATIONAL UNIVERSITY - Valerii Budak; Svitlana Zaskaleta (National Academy of Educational Sciences of Ukraine, 2019)
The article analyzes the problem of ensuring the quality of higher education. Ukraine aims to be in the European trend towards modernization of higher education, Ensuring the quality of higher education is much planned and at the same time the availability of the necessary resources (academic and administrative staff, students, academic and administrative leaders; financial, material, informational, scientific, educational resources etc.); organization of educational process that most adequately reflect modern trends in the development of national and world economy and education; the control of educational activities at the higher education sector and the quality of training of specialists at all stages of training and at all levels: the higher education institution, for higher education in different national and international (European) level. Quality assurance requires a lot of preparatory work. This is an extended process that requires continuous improvement of the achieved performance. Key components of the internal quality assurance system of higher education at the university is to ensure the quality of education at the university, processes of quality assurance in education teaching and learning; approval monitoring and periodic review of programs for assessing the quality of teaching staff, educational resources and support for students of information systems. The Concept of University Development is based on developed student-centered approach in education, which is a condition of the Bologna process.